2015
DOI: 10.1016/j.tbs.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities in developing urban modal shift

Abstract: Agriculture and Engineering, Newcastle upon Tyne NE1 7RU, UK * Contact: paul.batty2@ncl.ac.uk; +44 (0) 191 208 8657 Abstract Continued urbanisation, and the resultant increase in urban trips, presents one of the greatest challenges to the environmental, economic and social sustainability of society. Given that the modal split between transport modes has remained relatively unaltered in recent decades, this suggests that the levels of private car usage will lead to even greater levels of congestion and air poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 98 publications
3
64
0
1
Order By: Relevance
“…The importance of intermodal integration is part of this context [18]. This includes the availability of integrated and customized transportation in specific situations; the encouraged use of vehicles that use clean energy, such as electric cars and cycling; and other sustainable alternatives complementary to the traditional public transport [1,2,10,[19][20][21].…”
Section: Sustainable Urban Mobility Challengesmentioning
confidence: 99%
“…The importance of intermodal integration is part of this context [18]. This includes the availability of integrated and customized transportation in specific situations; the encouraged use of vehicles that use clean energy, such as electric cars and cycling; and other sustainable alternatives complementary to the traditional public transport [1,2,10,[19][20][21].…”
Section: Sustainable Urban Mobility Challengesmentioning
confidence: 99%
“…An extensive body of knowledge has shown that the passengers' perception on the transit system's service is related to their preference of taking the system. We may even conclude that the transit system's service is the first thing that is concerned by researchers when trying to understand the patronage and passengers loyalty of a transit system (Sharaby & Shiftan, 2012;Hensher & Li, 2012;Batty et al, 2015;Chakrabarti & Giuliano, 2015;Van Lierop & El-Geneidy, 2016;Satiennam et al, 2016;Chakrabarti, 2017;Fearnley et al, 2017). The passengers' perception of the rapid transit system's service encompasses both quantifiable and less-quantifiable components.…”
Section: Passengers' Perception Of Bus Rapid Transit (Brt) System's Smentioning
confidence: 99%
“…However, notable levels of modal shift are very difficult to be achieved on a long-term basis, due to the numerous societal and political challenges. These are discussed further by Batty et al [22], who analyse how best to attract people to public transport and dissuade car usage using 'push' and 'pull' mechanisms. This highlights the necessity for significant improvements in the public transport system as a whole, in terms of quality, capacity and level of integration, to help remove the perception that public transport is unclean, unreliable and of low comfort [23][24][25].…”
Section: Shifting Peak Travel To Facilitate Modal Shiftmentioning
confidence: 99%